Finansowanie ochrony zdrowia z funduszy strukturalnych Unii Europejskiej - Bromber, Piotr (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
Accepting the argument that the financial means dedicated to health protection are limited, the author of the paper emphasizes the need to use external sources of financing, in this case European Union structural funds. This paper attempts to answer the question of to what extent the sources from the European Regional Development Fund, and the European Social Fund, have influenced, or can influence the improved efficiency of the health protection system in Poland. The paper begins with the fundamental notions of health protection, the levels and forms of the delivery of health services, the subject range of the system (including the catalogue of beneficiaries), and the sources of finance. The most important (in the author’s opinion) current problems related to the organization and financing of health protection are also mentioned. Next, a general description of selected operating programs is presented with the examples of health protection projects financed from the structural funds that have already been implemented. The opportunities to fund these types of projects under the present financial perspective are also indicated. The subject matter of a detailed analysis presented in the paper concerns the Lubuskie province.